Boganmeldelser - Dan Frände; Anette Storgaard; Matti Joukamaa; Cornelius Larsen; Børge Dahl; Astrid Skretting; Elmo Due; Peter Garde; Torbjörn Thedéen; Jacob Hilden Winsløw (Nordisk Tidsskrift for Kriminalvidenskab)
Book reviews